2015
DOI: 10.3386/w20911
|View full text |Cite
|
Sign up to set email alerts
|

Does Competition Eliminate Discrimination? Evidence from the Commercial Sex Market in Singapore

Abstract: The street sex worker market in Geylang, Singapore is highly competitive. Clients can search legally at negligible cost. Sex workers discriminate based on client ethnicity despite an excess supply of sex workers. Workers are more (less) likely to approach and ask a higher (lower) price of Caucasians (Bangladeshis), based on their perceived willingness to pay. They avoid Indians, set a significantly higher price and are less likely to reach an agreement with them, suggesting that Indians face taste discriminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The first author and his team of enumerators collected the second dataset in 2015 and 2016 where they traced the borrowing transactions made by the same group of borrowers from 2014 to 2016. See Leong et al (2016) and Li et al (2017) for examples of the academic work that the first author had done on the underground economy.…”
Section: D1 Data Collection and Methodologymentioning
confidence: 99%
“…The first author and his team of enumerators collected the second dataset in 2015 and 2016 where they traced the borrowing transactions made by the same group of borrowers from 2014 to 2016. See Leong et al (2016) and Li et al (2017) for examples of the academic work that the first author had done on the underground economy.…”
Section: D1 Data Collection and Methodologymentioning
confidence: 99%
“…Hence, examining the wage income inequality and its drivers have important implications for understanding the changes in overall income inequality in urban China. In addition to Hukou (Zhang, 2010;Zhu, 2016), studies found that gender (Li and Li, 2008;Tang and Long, 2013), education (Chi et al, 2011;Gustafsson and Wan, 2020;Luo, 2018), industry and enterprise ownership (Chen et al, 2010;Chi et al, 2011) all have significant effects on wage disparities, but the extent to which these variables contribute to inequality varies across time. Prior to and shortly after the privatization of state-owned enterprises (SOEs) and the labor market reform in the 1980s, workers employed in SOEs and SOE-controlled industries enjoyed higher wage premiums due to monopolies (Chen et al, 2010;Chi et al, 2011).…”
Section: Figure 1 Per Capita Gdp and National Gini Indexmentioning
confidence: 99%
“…This literature has focused on the labor market (wage and employment differences), covering either the gender dimension (Ashenfelter & Hannan, 1986;Black & Strahan, 2001;Hellerstein, Neumark & Troske, 2002;Black & Brainerd, 2004), or the racial dimension (Peoples & Talley, 2001;Levine, Levkov & Rubinstein, 2008;Hirata & Soares, 2016). An exception is the study by Li, Lang & Leong (2017), which analyzes the sex market in Singapore, finding that price discrimination in this market persists despite competition. 6 To the best of our knowledge, this is the first paper that tests the impact of competition on price discrimination in an agricultural product market using a field experiment in a natural setting with regular participants.…”
Section: Introductionmentioning
confidence: 99%